Exploring Vespa Motorcycle Purchasing: Brand Image, Features, and Emotional Desire: Pengaruh Citra Merek, Fitur, dan Keinginan Emosional terhadap Keputusan Pembelian: Studi Kuantitatif pada Sepeda Motor Vespa di Kota Sidoarjo - Basysyar Hasna; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate the impact of brand image, features, and emotional desire on the purchase of Vespa motorcycles in Sidoarjo City, using a descriptive research design and quantitative methodology. A probability sampling technique was employed, and data were collected through questionnaires distributed to 97 Vespa motorcycle consumers. The obtained data were analyzed using multiple linear regression in SPSS version 22 for Windows. The results of validity and reliability tests indicated that all variables and questions were valid and reliable. The findings revealed that brand image, features, and emotional desire had a positive and significant influence on purchasing decisions. Thus, the study highlights the importance of these factors in shaping consumer behavior when purchasing Vespa motorcycles. These results have significant implications for marketers and businesses in enhancing their brand strategies and product features to attract and retain customers in the motorcycle market. Highlights: Brand image, features, and emotional desire significantly influence purchase decisions of Vespa motorcycles in Sidoarjo City. Quantitative study using probability sampling technique and questionnaire distribution to 97 Vespa motorcycle consumers. Findings have implications for marketers to enhance brand strategies and product features for attracting and retaining customers in the motorcycle market. Keywords: Brand Image, Features, Emotional Desire, Purchase Decision, Vespa Motorcycles.